Application of Social Cognitive Theory on Factors Related to Alcohol Consumption in Adolescents: Meta-Analysis - Hana Fathiya Dasairy; Argyo Demartoto; Hanung Prasetya (Journal of Health Promotion and Behavior, 2024)
Background: Alcoholic drinks are all types of drinks that contain ethanol. In several countries, alcohol is a drink that is easy to obtain, so it tends to be abused a lot. Continuous alcohol consumption can lead to alcohol dependence. The purpose of this research is to analyze the application of social cognitive theory about the factors that influence alcohol consumption in adolescents. Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: Teenagers. Intervention: anxiety, drinking parents and drinking friends. Comparison: No anxiety, no drinking parents, and no drinking friends. Outcome: Consumption of alcoholic beverages. The online databases used are: PubMed, Google Scholar, Science Direct, and Scopus with the keywords “factors associated” AND “alcohol consumption” AND “anxiety” OR “parents alcohol consumption” OR “peers alcohol consumption” AND “adolescents” AND " cross-sectional." The inclusion criteria for this study were complete articles using cross-sectional research, published years from 2013-2023. Data analysis used RevMan 5 software. Results: A total of 16 cross-sectional studies from several countries namely Ethiopia, Canada, United States, Taiwan, South Africa, Buthan, Myanmar, Uganda, Thailand, Zambia, Brazil, Ghana, and Iran were selected for systematic review and meta-analysis. The results of the meta-analysis showed that adolescents with anxiety had the possibility of consuming alcohol 1.57 times higher than adolescents who were not anxious (aOR= 1.57; 95% CI= 1.30 to 1.89; p< 0.001), adolescents whose parents drank had a probability of consuming alcohol 1.53 times higher than adolescents whose parents do not drink (aOR=1.53; 95%CI= 1.23 to 1.89; p= 0.001), adolescents whose friends drink have the possibility of consuming alcohol 2.63 times higher than adolescents whose friends are not drinkers (aOR=2.63 ; 95%CI= 1.59 to 4.35; p= 0.002). Conclusion: Teenagers with anxiety, have drinking parents, and have drinking friends are more likely to consume alcohol.